ANALISIS KEANDALAN AFTERBURNER ENGINE J85-GE- 21 PESAWAT F-5 E/F TNI AU - Norontoko
The afterburner is a very important system in the F-5 E/F aircraft in order to succeed the missions. In the year of 2005 untill 2007 most of aircraft failures were caused by engine problem, and afterburner alone contributes up to 61% to the total engine failures. The data used in the research come from the flight line troubleshooting records for the period of January 2005 and December 2007. Data evaluation and analysis using Weibull distribution and Fault Tree Analysis are carried out to determine the reliability of the components. The objectives of the analysis is to identify recommendations to improve the reliability. The basic of the analysis are literature studies and interview with competent persons. The data evaluation shows a very low afterburner reliability. This is caused by the low reliability of the components in the system. The failure characteristic shown by the distribution do not match with the characteristic of the failure modes. All of the components show a negative exponential distribution of failure. This is probably caused by abnormality of other components in the system. The interviews also results in suggestions on some applicable testing method to increase the reliability of the components.